Implementasi Rancang Bangun Water treatment system dalam Program Kuliah Kerja Nyata di Desa Cibuluh, Kecamatan Tanjungsiang, Kabupaten Subang - Budiyarto, Aris; Sunarya, Adhitya Sumardi; Lilansa, Noval; Aminah, Siti; Erdani, Yuliadi; Pratama, Rizqi Aji; Suryatini, Fitria (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
The escalating demand and excessive consumption of water resources have led to pollution and elevated water pressure, adversely impacting public health and environmental sustainability. Cibuluh Village possesses significant potential regarding water sources due to its proximity to seven rivers, ensuring a relatively high-water availability. However, this potential has not been fully realized due to the inadequate water resource treatment and management infrastructure. The absence of appropriate technology for water management has resulted in persistent challenges for the residents of Cibuluh Subang Village in accessing clean water. Consequently, the service has been implemented in four distinct stages: analysis of community needs, design and manufacturing of systems, implementation of programs and tool manufacturing, and testing of tools followed by field implementation. The test results revealed that the water filtration system exhibited a TDS reading of 91, indicating a high particle content. Despite these challenges, the service has led to the design and implementation of water purification systems, increased community engagement in addressing water quality issues, and the development of instructional documents on clean water usage